Democratic Republic of the Congo : Staff Report for the 2022 Article IV Consultation, Second Review Under the Extended Credit Facility Arrangement, Request for Modifications of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report, and Statement by the Executive Director for the Democratic Republic of the Congo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Considerable macroeconomic gains were achieved in 2021: the economic rebound was stronger than envisaged, driven by the non-extractive sector; CPI inflation declined to 5.3 percent year-on-year, accompanied by a stable exchange rate as the central bank stopped providing financing to the government; and an improved external position supported reserves accumulation. The 2021 fiscal outturn was also better-than-projected although domestic arrears accumulated. Despite excess liquidity, the banking sector faces vulnerabilities. The war in Ukraine is pushing up the cost of living and rising the fiscal costs associated with the fuel subsidy. Despite this and deteriorating global economic prospects, the outlook remains favorable and provides opportunities to consolidate macro stability and scale up structural reforms, though significant downside risks remain, and severe fragility persists.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Congo, Democratic Republic of the